A Systematic Review of the Scope and Patterns of Green Consumption in Sub-Saharan Africa - Traoré, L.; Belinga, B.; Lescuyer, G. (MDPI, 2023)
Despite the importance of “green consumption”, it has received little attention in sub-Saharan Africa. To address this gap, a systematic review of the scientific literature was conducted on the patterns of green consumption in this region using three parameters: green consumption, behaviour, and location. Forty-eight articles and publications were identified between 2010 and 2021 on Scopus, Web of Science, Google Scholar and grey literature. Scientific literature on green consumption in sub-Saharan Africa has expanded over the last five years, but it focuses primarily on emerging countries (Republic of South Africa and Nigeria) and the upper social classes. Most articles used the theory of planned behaviour as a theoretical framework. Green consumption of food and agricultural products are the most studied, with 14 articles. Energy, cosmetics, tourism, and textiles are each the subject of three specific publications. The emergence of middle-class consumers in sub-Saharan Africa is likely to contribute to the expansion of green consumption for a broad spectrum of goods and services.